2002
DOI: 10.1097/00004647-200207000-00014
|View full text |Cite
|
Sign up to set email alerts
|

[2,4-13C2]-β-Hydroxybutyrate Metabolism in Human Brain

Abstract: SummaryInfusions of [2,[4][5][6][7][8][9][10][11][12][13] C 2 ]-β-hydroxybutyrate and 1 H-13 C polarization transfer spectroscopy were used in normal human subjects to detect the entry and metabolism of β-hydroxybutyrate in the brain. During the 2-hour infusion study, 13 C label was detectable in the β-hydroxybutyrate resonance positions and in the amino acid pools of glutamate, glutamine, and aspartate. With a plasma concentration of 2.25 ± 0.24 mmol/L (four volunteers), the apparent tissue β-hydroxybutyrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 27 publications
7
51
0
Order By: Relevance
“…The b-hydroxybutyrate infusion therefore caused a resetting between the CBF and the cerebral metabolism of oxygen and glucose. We observed no decrease in glucose metabolism and no substitution of glucose by ketone bodies for the oxidative metabolism, as has been shown in humans both during short-term fasting (Hasselbalch et al, 1994) as well as during ketone body infusion (Hasselbalch et al, 1996;Pan et al, 2002), indicating a possible species difference. The arteriovenous differences for b-hydroxybutyrate during infusion of b-hydroxybutyrate were negligible -0.02 mmol/ L (s.d.…”
Section: Alterations In Cerebral Metabolismsupporting
confidence: 79%
“…The b-hydroxybutyrate infusion therefore caused a resetting between the CBF and the cerebral metabolism of oxygen and glucose. We observed no decrease in glucose metabolism and no substitution of glucose by ketone bodies for the oxidative metabolism, as has been shown in humans both during short-term fasting (Hasselbalch et al, 1994) as well as during ketone body infusion (Hasselbalch et al, 1996;Pan et al, 2002), indicating a possible species difference. The arteriovenous differences for b-hydroxybutyrate during infusion of b-hydroxybutyrate were negligible -0.02 mmol/ L (s.d.…”
Section: Alterations In Cerebral Metabolismsupporting
confidence: 79%
“…The dynamic enrichment pattern is nearly identical to that observed when [1-13 C]glucose is the infused substrate (e.g., see the study by Pan et al (2002)). In addition to the enriched amino acids, 13 C-labeled acetone was also observed during 13 C-BHB infusion ( Figure 3B; Supplementary Figure S1A), a product not observed during infusions of other substrates, such as [1,6-13 C 2 ]glucose or [2-13 C]acetate (Supplementary Figure S1B and C).…”
Section: Baselinesupporting
confidence: 75%
“…Increased astroglial acetate metabolism has been observed in mice maintained on a ketogenic diet possibly reflecting adaptation to prolonged ketonemia (Melo et al, 2006;Yudkoff et al, 2005). In contrast, a study of acute hyperketonemia in overnight-fasted humans (Pan et al, 2001(Pan et al, , 2002 infused intravenously with [2,4-13 C 2 ]-D-BHB revealed a pattern of brain glutamate and glutamine labeling similar to that from [1-13 C]glucose, indicating that oxidation of BHB, like glucose, occurred mostly in neurons-conclusions in line with results of early 14 C-labeled BHB tracer studies (Hawkins et al, 1986). Although brain utilization of ketone bodies is increased by fasting, contradictory findings have appeared on the effects of ketone bodies on brain glucose consumption.…”
mentioning
confidence: 99%
“…These fats are converted to the ketone bodies β-hydroxybutyrate, acetoacetate, and acetone, which represent an alternative energy source to glucose. In comparison with glucose, ketone bodies have a higher inherent energy (Pan et al, 2002;Cahill and Veech, 2003). In adults, glucose is the preferred substrate for energy production, particularly by the brain.…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…In addition, ketone bodies, especially acetoacetate, are preferred substrates for the synthesis of neural lipids. Ketone bodies readily cross the blood-brain barrier either by simple diffusion (acetone) or with the aid of monocarboxylic transporters (β-hydroxybutyrate, acetoacetate), whose expression is related to the level of ketosis (Pan et al, 2002;Pierre and Pellerin, 2005).…”
Section: Ketogenic Dietmentioning
confidence: 99%